2000
DOI: 10.1243/1350650001543016
|View full text |Cite
|
Sign up to set email alerts
|

Film thickness predictions for elastohydrodynamic elliptical contacts over a wide range of radius ratios with consideration of side starvation

Abstract: The paper presents numerical solutions obtained for a wide range of elliptical elastohydrodynamic lubrication (EHL) problems. The conditions considered encompass relative principal radii of curvature ratios from 20:1 with entrainment in the minor axis direction, to 50:1 with entrainment in the major axis direction. The problems considered derive from investigations of practical machine elements where the width of contact (perpendicular to entrainment) is limited by the extent of the metal surfaces on either si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 9 publications
3
18
0
Order By: Relevance
“…Sharif, et al (44) have performed the most recent study on the effect of ellipticity of an EHD contact on film thickness. The range of ratio of principal curvatures considered in their work is the most extensive to date but still does not encompass the value of the present study, although its limit is closer to that of the present study than that of Eq.…”
Section: Validity Of Micro-ehd Film Thickness Prediction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sharif, et al (44) have performed the most recent study on the effect of ellipticity of an EHD contact on film thickness. The range of ratio of principal curvatures considered in their work is the most extensive to date but still does not encompass the value of the present study, although its limit is closer to that of the present study than that of Eq.…”
Section: Validity Of Micro-ehd Film Thickness Prediction Methodsmentioning
confidence: 99%
“…13, it appears that the minimum film thickness for the longitudinally rough surface (defined by the film at the peak of the asperity) can be accurately predicted from the corresponding smooth elliptical micro-contact by (44) 0.02 < R y / R x < 20 Dowson and Hamrock (38) 0.955 <R y / R x < ∞ allowing for the effect of the ridge geometry, R y , in the inlet and for the ridge load. Finally, it is important to note that this micro-EHD film thickness prediction technique for longitudinal roughness will be valid only at extremely low lambda ratios as in the present study, within the mixed lubrication regime, since it assumes that the ridges are independent and that there is no hydrodynamic lift from lubricant in the valleys.…”
Section: Validity Of Micro-ehd Film Thickness Prediction Methodsmentioning
confidence: 99%
“…This is illustrated by comparing the authors results with the results for narrow contacts presented in reference [17], see Tables 1 to 3. To reduce the effects of the size of the domain only results are presented for load conditions which are sufficiently well in the (piezoviscous)-elastic regime (i.e.…”
Section: Resultsmentioning
confidence: 72%
“…Therefore, all contact results of a given curve are for contacts with the same maximum Hertzian pressure. It can be observed that for each [17] for narrow elliptic contacts, and references therein. It is also clearly shown in Fig.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation